Survival of Patients with Acute Heart Failure and Mid-range Ejection Fraction in a Developing Country - A Cohort Study in South Brazil - Petersen, Lucas Celia; Danzmann, Luiz Claudio; Bartholomay, Eduardo; Bodanese, Luiz Carlos; Donay, Brenda Gonçalves; Magedanz, Ellen Hettwer; Azevedo, Adriana Vier; Porciuncula, Gustavo Farias; Miglioranza, Marcelo Haertel (Arquivos brasileiros de cardiologia, 2021)
Heart Failure with mid-range Ejection Fraction (HFmEF) was recently described by European and Brazilian guidelines on Heart Failure (HF). The ejection fraction (EF) is an important parameter to guide therapy and prognosis. Studies have shown conflicting results without representative data from developing countries. To analyze and compare survival rate in patients with HFmEF, HF patients with reduced EF (HFrEF), and HF patients with preserved EF (HFpEF), and to evaluate the clinical characteristics of these patients. A cohort study that included adult patients with acute HF admitted through the emergency department to a tertiary hospital, reference in cardiology, in south Brazil from 2009 to 2011. The sample was divided into three groups according to EF: reduced, mid-range and preserved. A Kaplan-Meier curve was analyzed according to the EF, and a logistic regression analysis was done. Statistical significance was established as p < 0.05. A total of 380 patients were analyzed. Most patients had HFpEF (51%), followed by patients with HFrEF (32%) and HFmEF (17%). Patients with HFmEF showed intermediate characteristics related to age, blood pressure and ventricular diameters, and most patients were of ischemic etiology. Median follow-up time was 4.0 years. There was no statistical difference in overall survival or cardiovascular mortality (p=.0031) between the EF groups (reduced EF: 40.5% mortality; mid-range EF 39.7% and preserved EF 26%). Hospital mortality was 7.6%. There was no difference in overall survival rate between the EF groups. Patients with HFmEF showed higher mortality from cardiovascular diseases in comparison with HFpEF patients. (Arq Bras Cardiol. 2021; 116(1):14-23).